Implementation of Academic Supervision in Elementary School - Karamoy, Claudya; Lumapow, Harol R.; Pangkey, Richard D. H. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The purpose of this study was to obtain descriptive and analytical results regarding academic supervision planning by the principal of Citra Kasih Elementary School Manado, the implementation of academic supervision in the process at Citra Kasih Elementary School Manado, the follow-up of academic supervision results at Citra Kasih Elementary School Manado, and the obstacles to academic supervision at Citra Kasih Elementary School Manado. The method used in this study was naturalistic inquiry research, meaning it was carried out in natural conditions. This study resulted in the supervision planning being adjusted to the central/foundation curriculum, as was the format used. Supervision was carried out by directly visiting the class while the teachers were teaching. Through supervision, the principal and his team could observe the direct performance of the teachers concerned. The results of the evaluation form were not only archived by the supervision team, but also given to the teachers to be used as input for improvements in the learning process.